Molecular Analysis of Protein-Protein Interactions in the Ethylene Pathway in the Different Ethylene Receptor Subfamilies - Berleth, Mareike; Berleth, Niklas; Minges, Alexander; Hänsch, Sebastian; Burkart, Rebecca Corinna; Stork, Björn; Stahl, Yvonne; Weidtkamp-Peters, Stefanie; Simon, Rüdiger; Groth, Georg (Frontiers in Plant Science, 2019)
Signal perception and transmission of the plant hormone ethylene are mediated by a family of receptor histidine kinases located at the Golgi-ER network. Similar to bacterial and other plant receptor kinases these receptors work as dimers or higher molecular weight oligomers at the membrane. Sequence analysis and functional studies of different isoforms suggest that the ethylene receptor family classifies into two subfamilies. In Arabidopsis, the type-I subfamily has two members (ETR1 and ERS1) and the type-II subfamily three members (ETR2, ERS2 and EIN4). Whereas subfamily-I of the Arabidopsis receptors and their interactions with downstream elements in the ethylene pathway has been extensively studied in the past, related information on subfamily-II is sparse. In order to dissect the role of type-II receptors in the ethylene pathway and to decode processes associated with this receptor subfamily on a quantitative molecular level, we have applied biochemical and spectroscopic studies on purified recombinant receptors and downstream elements of the ethylene pathway. To this end, we have expressed and purified ETR2 as a prototype of the type-II subfamily, ETR1 for the type-I subfamily and downstream ethylene pathway proteins CTR1 and EIN2. Functional folding of the purified receptors was demonstrated by CD spectroscopy and autokinase assays. Quantitative analysis of protein-protein interactions (PPI) by microscale thermophoresis revealed that ETR2 has similar affinities for CTR1 and EIN2 as previously reported for the subfamily-I prototype ETR1 suggesting similar roles in PPI-mediated signal transfer for both subfamilies. We also used in planta fluorescence studies on transiently expressed proteins in Nicotiana benthamiana leaf cells to analyze homo- and heteromer formation of receptors. These studies show that type-II receptors as wells as the type-I receptors form homo- and heteromeric complexes at these conditions. Notably, type-II receptor homomers and type-II:type-I heteromers are more stable than type-I homomers as indicated by their lower dissociation constants obtained in microscale thermophoresis studies. The enhanced stability of type-II complexes emphasizes the important role of type-II receptors in the ethylene pathway.